The Creators of Inside Money A New Monetary Theory - Thomas, D. Gareth (Springer International Publishing, 2018)
This book develops a new monetary model based on the medium of exchange. It builds on existing theory in money, banking and finance to present a more precise formulation of the money supply chain to derive a fully dynamic model. It is supported by the inclusion of case studies, graphs and figures to give an international setting and application.